Analisis Pengaruh Pertumbuhan Ekonomi, IPM, Dan Pengangguran Di Kalimantan Tengah Pada Tahun 2010-2019 - Achmad Hidayat; Alexandra Hukom (Institut Nalanda, 2023)
This study focuses on the factors that influence the poverty rate in 15 regencies/cities in Central Kalimantan from 2010 to 2019. The type of research conducted is descriptive quantitative using secondary data sourced from the Central Bureau of Statistics (BPS). The regression analysis of numerical data poverty rate in South Kalimantan and Central Kalimantan found that the economic growth variable did not significantly influence the poverty rate in Central Kalimantan. However, the variables Human Development Index and unemployment significantly influence the poverty rate of the two states. The poverty variable has a significant adverse effect on the poverty level. Human resource development strategies and policies focusing on education, health, and people's incomes are vital to reducing poverty.